The Subject of Gender : Daughters and Mothers in Urban China. - Evans, Harriet (Asian voices., 2007)
Author Harriet Evans discusses mother-daughter relationships in urban China, reflecting on how women make sense of the shifts in practices and representations of gender that frame their lives, and how their self-identification as mothers and daughters contributes to the redefinition of those practices. Based on the memories and experiences of educated and professional women of different ages, the mother-daughter relationship is discussed through various themes: separation, communication, domestic/public boundaries, male privilege, the sexed body, reproduction and filial responsibilities.